Renal-clearable nickel-doped carbon dots with boosted photothermal conversion efficiency for multimodal imaging-guided cancer therapy in the second near-infrared biowindow - Tian, Boshi (2022)
Photothermal agents with absorption in the second near-infrared (NIR-II) biowindow have attracted increasing attention for photothermal therapy (PTT) on account of their deeper tissue penetration capacity. However, most of the current NIR-II photothermal agents exhibit low photothermal conversion efficiency (PCE) and long-term biotoxicity. To overcome these shortcomings, herein, nickel and nitrogen co-doped carbon dots (Ni-CDs, ≈4.6 nm) are prepared via a facile one-pot hydrothermal approach for imaging-guided PTT in the NIR-II window. The Ni-CDs exhibit significant absorption in the NIR-II region with a distinguished PCE as high as 76.1% (1064 nm) and have excellent photostability and biocompatibility. Furthermore, the Ni-CDs can be employed as photothermal, photoacoustic, and magnetic resonance imaging contrast agents because of their outstanding photothermal effect and instinctive paramagnetic feature. The Ni-CDs demonstrate significant PTT efficacy of tumor upon 1064 nm irradiation with a low power density (0.5 W cm−2). The Ni-CDs can be eliminated from the body via a renal filtration pathway, thereby minimizing their long-term biotoxicity. Therefore, this work provides a simple and feasible approach to develop photothermal agents with remarkable PCE in the NIR-II region, presenting good biosafety for multimodal imaging-guided PTT of tumor.